Clinical and Surgical Management of an Aggressive Cherubism Treated with Autogenous Bone Graft and Calcitonin. (26th October 2010) - Fernandes Gomes, Mônica; Ferraz de Brito Penna Forte, Lilibeth; Hiraoka, Cybelle Mori; Augusto Claro, Flávio; Costa Armond, Mônica
Abstract : Cherubism is a rare autosomal-dominant inherited syndrome and is usually self-limiting; it starts in early childhood and involutes by puberty. It is a benign fibroosseous disease, characterized by excessive bone degradation of the upper and lower jaws followed by development of fibrous tissue masses. The purpose of this clinical report is to describe a rare and aggressive form of cherubism on an adult female patient that has been treated in our Bioscience Center for Special Health Care Needs-CEBAPE. The patient was firstly submitted to the surgical procedure with partial curettage of the lesion, and the cavity was filled with autogenous cancellous bone and bone marrow grafts. Furthermore, the support treatment used was the administration of salmon calcitonin by nasal spray during the first year after the preconized procedure. At 4-year followup, we confirmed the stomatognathic system improvement and esthetic rehabilitation, which led to a significant increase in the patient's quality of life.